PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TINGKAT KEPATUHAN PAJAK DENGAN GENDER SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERBANKAN - Joshua Bram; Dul Muid (Diponegoro Journal of Accounting, 2023)
Tax is the largest income in a country. Taxes are used by the government to fund national development that takes place continuously and continuously which aims to improve people's welfare. This study aims to provide empirical evidence and analyze CSR disclosure has a positive effect on the level of tax compliance of a company and the effect of the gender variable on the level of tax compliance which can be a moderator between CSR disclosure on the level of corporate tax compliance. The object of this research is a banking company in indonesia from 2016-2019. This analysis uses Moderated Regression Analysis (MRA). Research shows that there is no significant effect on CSR on tax compliance, and gender is not able to significantly moderate the effect of CSR on tax compliance in Banking company in Indonesia.